Excessive daytime sleepiness in myotonic dystrophy: a narrative review - Hoxhaj, Domeniko; Pascazio, Alessia; Maestri, Michelangelo; Ricci, Giulia; Fabbrini, Monica; Torresi, Francesca Buracchi; Siciliano, Gabriele; Bonanni, Enrica (Frontiers in Neurology, 2024)
This review aims to provide a comprehensive analysis of excessive daytime sleepiness (EDS) in myotonic dystrophy type 1 (DM1) and type 2 (DM2). EDS is a common and debilitating symptom in both forms of myotonic dystrophy, significantly impacting patients' quality of life. Polysomnographic studies have revealed a prominent dysregulation of REM sleep in DM1, suggesting a possible narcoleptic-like phenotype and alterations in NREM sleep, such as increased sleep instability and impaired delta power dissipation, that contributes to daytime sleepiness. While sleep-disordered breathing (SDB) and respiratory dysfunctions are prevalent in DM1 and DM2, their direct correlation with EDS remains complex and inconclusive. The review focuses on the purpose of examining the current understanding of EDS in these conditions, the difficulty in correctly accessing it, the recent findings related to its etiology and prevalence, and a summary of potential therapeutic implications.